DEFORMATION PRACTICES OF SOCIAL REALITY INTEGRITY: OBJECTIFICATION OF DESIRES AS THE INHERITANCE OF CIVILIZATION PROGRESS - Yuliia Yu. Brodetskaya (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Objective. The interest of the article focuses on the analysis of the social integrity phenomenon and its deformation practices in the modern society. The character’s sociality of the modern era indicates serious problems and contradictions that actualize the possibility of social integrity. The cultural crisis, spiritual vacuum, updated existential problems of the modern humanity forces to turn to the problem of the integrity constructing and maintaining and social reality functioning, as well as to the mechanisms and practices of its deformation. Methodology. Thus, in the analysis of the above mentioned points the problem of desires is getting more relevant, and these desires are actively being invested by the civilization progress in the human life. As simulacra of the natural mechanisms of individual activity (needs) desires help to transform the personality harmonious development process (cultural consumption) in a destructive civilization strategy – consumerism. Under these conditions consumption is losing its traditional meaning. From the natural processes of meeting the needs and developing the world it is transforming into a total destructive act that implements certain desires. Consumption grows borders of the traditional practice (it has not been already determined only by food, clothes, car, etc.). It is turning into an active mass orientation; practice of the materialization that is aimed to transform the surrounding world into a thing, a symbol of use. Thus, consumption transforms into a practice of total consumerism. The scientific novelty. In this context, the aim of the research is to analyze the destructive potential of consumerism, which nature is getting a real threat to the integrity of both individual world and social reality. This pattern of consumption determines the gap between a real purpose of the things and their contrived sense that gives them the desired effect (prestige, power, material wealth, etc.). In this situation, we can see updating of the tendency when things lose their true purpose, and man loses his active role. He is no longer a creator of qualitatively new products that fill his life with meaning. He is a conformal trimmer who routinely plays ersatz and fills his live with them. Material aspects rather than spiritual ones determine the value and meaning of human’s life, they represent a desired object that he wants to receive. His choice is ruled not by creative work, but by the civilization "benefits" bondage. Conclusions. Such deformation of harmonious development of the man and society, and of the traditional order transforms nature of the human relations to turn them into a banal practice of consumerism – usage. The desire to own, exploit, use makes a human to devalue surrounding reality and its members, turns a human into a homo economics, who calculates his circle of friends, communication, relationships. Exactly such "commercialization of relationship" overcomes the limits of the economic, political and legal spheres and encroaches on the family, friendship sphere to determine the whole character of the modern society.